Analysis of the Fanatic Attitudes of K-Pop Fans and Their Implications for the Decadence of Morals of Singaperbangsa University Karawang Students - Najwa Aulia Maharani; Debibik Nabilatul Fauziah; Neng Ulya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Fanaticism or fanaticism is the nature (natural) of humans which reasons that at the level of society you can find individuals or groups who have fanatical attitudes. If traced deeply through the problem, fanaticism means blind love for those you like and antipathy towards things you don't like and is related to feelings of excessive self-love (narcissism). This research aims to find out the fanatic attitudes that Unsika students have and their implications for moral decadence. The method used in this research is a descriptive qualitative method with data analysis techniques in the form of data collection, data reduction, data presentation, and drawing conclusions. Based on the results of observations and interviews conducted with the 6th ARMY Unsika, the fanaticism of K-Pop ARMY fans at Singaperbangsa University Karawang is divided into several categories, namely: (1) Excessive interest and love, (2) Consumptive behavior, (3) Envy. The implications of the fanaticism of K-Pop ARMY fans towards the decadence of morals of Singaperbangsa University Karawang students show that K-Pop ARMY fans at Unsika have bad habits including: (1) Negligence in carrying out the commands of Allah SWT, (2) Mubazir, (3) Hasad.